2015
DOI: 10.3390/jcm4091761
|View full text |Cite
|
Sign up to set email alerts
|

Non-Proteinuric Diabetic Nephropathy

Abstract: Diabetic nephropathy patients traditionally show significant macroalbuminuria prior to the development of renal impairment. However, this clinical paradigm has recently been questioned. Epidemiological surveys confirm that chronic kidney disease (CKD) diagnosed by a low glomerular filtration rate (GFR) is more common in diabetic patients than in the non-diabetic population but a low number of patients had levels of proteinuria above that which traditionally defines overt diabetic nephropathy (>500 mg/g). The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 54 publications
2
28
0
Order By: Relevance
“…cohort is small and the diagnostic method was usually not renal biopsy, the results are in line with prior reports [6]. However, recent studies have shown that patients with biopsy-proven DN may be normoalbuminuric [18]. Thus, further studies with larger cohorts and ideally renal biopsy confirmation are necessary to find factors better predicting NDN in type 2 diabetic patients.…”
supporting
confidence: 84%
“…cohort is small and the diagnostic method was usually not renal biopsy, the results are in line with prior reports [6]. However, recent studies have shown that patients with biopsy-proven DN may be normoalbuminuric [18]. Thus, further studies with larger cohorts and ideally renal biopsy confirmation are necessary to find factors better predicting NDN in type 2 diabetic patients.…”
supporting
confidence: 84%
“…The results suggest that diabetes may be associated with direct tubular toxicity on renal tubular cells. This finding is notable and consistent with recent studies of patients with advanced CKD and diabetes who do not have significant proteinuria/glomerular dysfunction (16).…”
supporting
confidence: 81%
“…In a biopsy study of patients with Type 2 DM and CKD (eGFR <60 mL/min/1.73 m 2 ), normoalbuminuric patients were less likely to have typical glomerular changes of DN, but more likely to have arteriosclerosis and tubule-interstitial fibrosis alone [10]. Normoalbuminuric patients without the glomerular changes of DN may have progressive CKD, but this may be due to hypertension, obesity and intrarenal vascular disease rather than DN nephropathy, and the diagnosis can only be clarified by biopsy [11, 12]. Biopsy series of patients with atypical DN presentations (with or without proteinuria) demonstrated that 35–60% had other causes of glomerular disease, and up to 1/3 had nondiabetic renal disease only, including acute tubular necrosis, hypertensive nephrosclerosis and focal segmental glomerulosclerosis [13, 14].…”
Section: Discussionmentioning
confidence: 99%
“…The criteria are Grade B ‘moderately strong evidence’ recommendations, especially for patients with Type 1 DM. For Type 2 diabetics, micro- and macroalbuminuria are not as strongly predictive of typical diabetic glomerular changes on biopsy, and are not as strongly associated with retinopathy [8–10, 12, 15, 17]. Although the positive predictive value of retinopathy concurrent with macroalbuminuria is 67–100%, the negative predictive value is quite variable at 20–84% [3].…”
Section: Discussionmentioning
confidence: 99%